Method for the preparation of iron-based mofs by electron beam irradiation, and iron-based mofs and applications

CN117683240BActive Publication Date: 2026-10-27SHANGHAI UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311471320.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-07
Publication Date
2026-10-27
Estimated Expiration
2043-11-07

AI Technical Summary

Technical Problem

尽管如此,这些方法仍然需要特殊的封闭系统、高温条件和特殊设备,而且没有适用于制备多孔材料的方法

Benefits of technology

[0025]本申请合成了一种不同于普通水热法合成的铁基MOFs。持续的电子束与所合成的分子相互作用,使所合成分子之间化学键断裂改变了样品的形貌和尺寸,产生了丰富空位和缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117683240B_ABST
    Figure CN117683240B_ABST
Patent Text Reader

Abstract

The application discloses a method for synthesizing iron-based MOFs by electron beam irradiation, and steps of the method comprise the following steps: dissolving a salt containing Fe ions and an organic ligand into a solvent to obtain a uniform mixed solution; discharging air in the mixed solution; and performing controllable irradiation on the mixed solution by using a high-energy electron beam; and collecting a solid obtained after irradiation, so that the iron-based MOFs are obtained. The application further provides the iron-based MOFs obtained by the method and electrocatalytic application of the iron-based MOFs. In the formation process of the iron-based MOFs, the iron-based MOFs have rich vacancy defects due to continuous interaction between the electron beam and the synthesized molecules. The defects can not only serve as catalytic active sites, but also optimize the electronic structure of the material, accelerate charge transfer and improve intrinsic catalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electrocatalyst materials, and more particularly to a method for synthesizing iron-based MOFs (Fe-MOFs) materials by electron beam irradiation, the iron-based MOFs materials obtained by this method, and their applications. Background Technology

[0002] Electrochemical water splitting is one of the most promising methods for producing high-purity hydrogen and is considered a major direction for future hydrogen production. The electrochemical water splitting process involves two half-reactions: the oxygen evolution reaction (OER) and the hydrogen evolution reaction (HER). However, the scalable industrial application of electrochemical water splitting is limited by the slow kinetics of these two half-reactions.

[0003] Noble metal-based electrocatalysts exhibit high catalytic activity in HER and OER processes, but their high cost, low stability, and resource scarcity limit their practical application. In recent years, many non-noble metal-based catalysts have been developed, but their low conductivity, insufficient electrochemical active surface area, poor long-term stability, and susceptibility to deactivation of active sites in strong acid or alkaline electrolytes make achieving an efficient hydrogen cycle a difficult goal to achieve.

[0004] Metal-organic frameworks (MOFs) are a class of novel materials with extremely high porosity. Their tunable molecular cavities and functional properties make them indispensable advanced materials in industrial processes such as gas storage, separation, and catalysis. However, traditional MOF synthesis methods typically require high-temperature, high-pressure closed systems and long reaction times, which limits their industrial applications.

[0005] In recent years, methods such as microwave-assisted synthesis, ultrasonic synthesis, and surfactant synthesis have been increasingly used to accelerate the synthesis of MOFs. Nevertheless, these methods still require specialized closed systems, high-temperature conditions, and specialized equipment, and there is no method suitable for preparing porous materials. Summary of the Invention

[0006] To overcome the shortcomings of the existing technology, this application provides a method for preparing iron-based MOFs materials with excellent performance, simple preparation, and suitable for large-scale industrial production, as well as their applications.

[0007] The first aspect of this application is to provide a method for synthesizing iron-based MOFs by electron beam irradiation, the steps of which include:

[0008] Salts containing Fe ions and organic ligands are dissolved in a solvent to obtain a mixed solution;

[0009] The air in the mixed solution is removed, and the mixed solution is irradiated with an electron beam;

[0010] After irradiation, the collected solids yielded iron-based MOFs.

[0011] In a preferred embodiment, the iron ions in this application may be Fe. 3+ and / or Fe 2+ Preferably, the salt can be an inorganic acid salt or an organic carboxylate salt, such as ferric chloride, ferrous chloride, ferrous sulfate, ferrous sulfate ammonium sulfate, ferric sulfate ammonium, ferric nitrate, ferrous nitrate, ferric acetate, ferrous acetate, ferric oleate, ferrous oleate, ferrous lactate, ferrous lactate, ferrous succinate, ferric oxalate, ferrous oxalate, ferric ammonium citrate, etc.

[0012] In a preferred embodiment, the organic ligand is preferably a compound containing at least two functional groups capable of complexing with Fe ions, especially a compound containing an aromatic ring, such as a dicarboxylic acid or more monocarboxylic acids, a hydroxyl-containing carboxylic acid, an amino acid, a compound containing an imidazole structure, a thiazole-containing compound, etc. Preferably, the organic ligand can be selected from: terephthalic acid, isophthalic acid, phthalic acid, trimellitic acid, trimellitic acid, trimellitic acid, 2-aminoterephthalic acid, 2-hydroxyterephthalic acid, 4-methyl-1,2-phthalic acid, 2-methyl-1,4-phthalic acid, 1,3,6,8-tetraenoic acid, 1,4,5,8-naphthalenetetracarboxylic acid, 1,4-naphthalenedicarboxylic acid, 2,7- Naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, p-aminobenzoic acid, 3-(aminomethyl)benzoic acid, 5-methylisophthalic acid, 5-hydroxyisophthalic acid, 4,4'-biphenyldicarboxylic acid, 3,3',4,4'-biphenyltetracarboxylic acid, p-hydroxymethylbenzoic acid, salicylic acid, tyrosine, imidazole, benzimidazole, dimethylimidazolium, imidazole[1,2-b]pyridazine, histamine, theophylline, histidine, purine, adenine, 6-hydroxypurine, 2-(1,3-thiazol-4-yl)benzimidazole, 4-azabenzimidazole, 4-amino-5-imidazolium carboxamide, 4,5-imidazolium dicarboxylic acid, 5,6-dimethylbenzimidazole, 2-methylbenzimidazole, 2-benzylbenzimidazole, (1H-imidazolium- 4-(hydroxymethyl)imidazolium, 2,4-diphenylimidazolium, 2-methylimidazolium, 2-methyl-4-nitroimidazolium, 2-methyl-3H-benzimidazole-5-carboxylic acid, 4-(hydroxymethyl)imidazolium, 4-hydroxyethylimidazolium, 4-aminoimidazolium, 2-propylbenzimidazole, 4-methyl-2-phenylimidazolium, 2-aminobenzimidazole, 2-ethyl-4-methylimidazolium, 2-acetylbenzimidazole, 2,6-diaminopurine, 1H-imidazolium-4-yl-formaldehyde, 1H-imidazolium-4,5-dicarboxylic acid dimethyl ester, thiazole, benzothiazole, naphtho[1,2-d]thiazole, 2-methylbenzothiazole, 2-aminothiazole, 2-aminobenzothiazole, 2-aminobenzothiazole-6-carboxylic acid, 2-amino- 6-Chlorobenzothiazole, 4-methyl-5-hydroxyethylthiazole, 2,4-dimethylthiazole, 4-methylthiazole, 4-phenylthiazole, thiazole-5-yl-formaldehyde, 2-amino-5-aldehyde thiazole, 2-phenylbenzothiazole, 2-amino-4-methylbenzothiazole, 4,5-dimethylthiazole, salicylic acid, 4-methylsalicylic acid, 1-hydroxy-2-naphthoic acid, 2-hydroxy-3-naphthoic acid, 5-aminosalicylic acid, 2,4-dihydroxybenzoic acid, 5,5'-methylenedisalicylic acid, 4,4'-methylenedi(3-hydroxy-2-naphthoic acid), 2,5-dihydroxyterephthalic acid, 5-formylsalicylic acid, 4-hydroxyisophthalic acid, 4-methoxy-1,3-phthalic acid, etc.

[0013] In a preferred embodiment, the solvent is preferably an aprotic polar solvent, such as N,N-dimethylformamide, dimethyl sulfoxide, acetone, methyl ethyl ketone, pyridine, acetonitrile, tetrachloromethane, etc.

[0014] In a preferred embodiment, the molar ratio of the Fe-containing salt, organic ligand, and solvent is preferably (1-10):(1-10):(10-1000); more preferably (1-10):(1-10):(50-800); and even more preferably (1-10):(1-10):(100-500).

[0015] In a preferred embodiment, during the electron beam irradiation process, the electron beam current intensity is preferably 0.1-50 mA, more preferably 0.3-40 mA, more preferably 0.5-30 mA, more preferably 0.7-25 mA, more preferably 1-20 mA, more preferably 3-15 mA, and more preferably 5-10 mA.

[0016] In a preferred embodiment, during the electron beam irradiation process, the electron beam irradiation dose is preferably 10-5000 kGy; more preferably 20-4000 kGy; more preferably 30-3000 kGy; more preferably 40-2000 kGy; more preferably 50-1000 kGy; more preferably 60-800 kGy; more preferably 70-600 kGy; more preferably 80-500 kGy; more preferably 90-400 kGy; more preferably 100-300 kGy, such as 120 kGy, 150 kGy, 180 kGy, 200 kGy, 230 kGy, 250 kGy, and 280 kGy.

[0017] In a preferred embodiment, the collected solid is washed with a second solvent, which may be selected from water, alcohol, phenol, ether, aldehyde, ketone, ester, tetrahydrofuran, hydrocarbon, acetonitrile, pyridine, carbon disulfide, etc. For example, it may be selected from: water, ethanol, methanol, isopropanol, phenol, diethyl ether, petroleum ether, propylene oxide, dioxane, acetone, methyl ethyl ketone, methyl butanone, methyl isobutyl ketone, methyl acetate, ethyl acetate, propyl acetate, benzene, toluene, chlorobenzene, pentane, octane, hexane, dichloromethane, chloroform, trichloropropane, dichloroethane, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, tetrahydrofuran, pyridine, carbon disulfide, etc.

[0018] In a preferred embodiment, the collected solid is washed with a second solvent and then dried. Preferably, the drying temperature does not exceed 100°C, more preferably does not exceed 80°C, more preferably does not exceed 70°C, and even more preferably does not exceed 60°C.

[0019] A second aspect of this application is to provide an iron-based MOF, preferably prepared by the method described in the first aspect of this application.

[0020] A third aspect of this application is to provide an electrocatalytic method or electrocatalytic device, using the iron-based MOFs as an electrocatalyst.

[0021] Preferably, the electrocatalysis is electrolysis, wherein the working electrode contains, and preferably is composed of, the iron-based MOFs, and the inert electrode is the counter electrode.

[0022] More preferably, the electrocatalyst is an electrochemical oxygen evolution catalyst.

[0023] More preferably, the iron-based MOFs serve as catalysts for the electrochemical oxygen evolution reaction.

[0024] Preferably, the electrochemical oxygen evolution is performed using an alkaline solution as the electrolyte, and the alkaline solution is preferably potassium hydroxide, sodium hydroxide, etc. More preferably, the electrochemical hydrogen evolution is performed using an alkaline tank for hydrogen production.

[0025] This application synthesizes an iron-based MOF that differs from those synthesized by conventional hydrothermal methods. The continuous interaction of the synthesized molecules with an electron beam causes the chemical bonds between the molecules to break, altering the morphology and size of the sample and generating abundant vacancies and defects.

[0026] When the iron-based MOFs synthesized in this application are used in water electrolysis, their unique surface charge state is beneficial for OH-. - Rapid adsorption allows it to act as a catalyst to accelerate the OER process. Furthermore, the abundant vacancies and defects generated under electron beam irradiation optimize the electronic structure, accelerate charge transfer, and enhance the intrinsic activity of the catalyst. Especially in alkaline media, it exhibits better OER performance compared to hydrothermal synthesis. Driven by 200 mA / cm² -2 It requires only 288mV of overpotential to achieve a current density, while also exhibiting excellent stability. Attached Figure Description

[0027] The accompanying drawings, which constitute a part of this application, are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an undue limitation of this application. In the drawings:

[0028] Figure 1 The XRD patterns of the iron-based MOFs contained in this application are shown.

[0029] Figure 2 The Raman spectra of the iron-based MOFs contained in this application;

[0030] Figure 3 Transmission electron microscope images of iron-based MOFs in this application;

[0031] Figure 4 OER polarization curves of iron-based MOFs prepared in Examples 1-3 and Comparative Examples 1-2;

[0032] Figure 5 This is a chronopotential curve of the iron-based MOFs of this application at 20 mA / cm³. Detailed Implementation

[0033] This application provides an iron-based MOF, its preparation method, and its application. To make the objectives, technical solutions, and effects of this application clearer and more explicit, the following detailed description is provided with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only for explaining this application and are not intended to limit this application.

[0034] It should be noted that the terms "first," "second," etc., in the specification, claims, and accompanying drawings of this application are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence. It should be understood that such data can be used interchangeably where appropriate. Furthermore, the terms "comprising" and "having," and any variations thereof, are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or apparatus that comprises a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products, or apparatuses.

[0035] Unless otherwise specified in the following content of this application, the raw materials used in the examples are all commercially available analytical grade products and have not undergone further purification.

[0036] Unless otherwise specified in the following content of this application, the phase composition of the prepared iron-based MOFs was analyzed by XRD-D / MAX2200V PV type X-ray diffractometer (Cu target, Kα rays as radiation source, incident wavelength...). The scanning range of 2θ = 5°-80° was characterized at a scanning rate of 8° / min.

[0037] Unless otherwise specified in the following content of this application, the morphology of the prepared iron-based MOFs was observed by a JSM-7500F scanning electron microscope of JEOL LTD, Japan, with an accelerating voltage of 20 kV.

[0038] Unless otherwise specified in the following content of this application, the transmission electron microscope used is the JEM-2100F from Nippon Electron Ltd.

[0039] Example 1

[0040] 1. Preparation of iron-based MOF electrocatalysts

[0041] (1) Prepare a mixed solution by mixing FeCl3·6H2O, terephthalic acid and N,N-dimethylformamide in a molar ratio of 1:1:280. Put the mixed solution into a vacuum-sealed bag and remove the air.

[0042] (2) Then the mixed solution was irradiated with an electron beam. The electron beam current intensity was set to 5 mA and the irradiation dose was 200 kGry, and the irradiated sample was obtained.

[0043] (3) The irradiated sample was washed three times with ethanol and deionized water respectively, and then placed in a vacuum drying oven and dried at 60 degrees Celsius for 12 hours to obtain the iron-based MOF electrocatalyst synthesized by electron beam irradiation.

[0044] 2. Preparation of KOH electrolyte

[0045] Dissolve 5.6 g of KOH in 50 mL of ultrapure water. After the KOH solution has completely dissolved and cooled, dilute to volume in a 100 mL volumetric flask.

[0046] 3. Preparation of Nickel Foam

[0047] A piece of nickel foam was immersed in a 1 mol / L hydrochloric acid solution and sonicated for 10 minutes. The surface was then treated with an acetone solution and sonicated for 10 minutes. Finally, it was sonicated with ethanol and deionized water for 30 minutes each.

[0048] 4. Preparation of the working electrode

[0049] Weigh 3 mg of iron-based MOF sample and disperse it in a mixed solution of 165 μL deionized water and 55 μL ethanol, then sonicate until homogeneous. Add 20 μL of Nafion and sonicate for 30 minutes. Slowly add 120 μL of the dispersion to pre-treated nickel foam using a pipette, and allow to dry in a vacuum oven for 2 hours to successfully prepare the iron-based MOF working electrode.

[0050] Example 2:

[0051] 1. Preparation of iron-based MOF electrocatalysts

[0052] (1) Prepare a mixed solution by mixing FeCl3·6H2O, isophthalic acid and N,N-dimethylformamide in a molar ratio of 1:1:280. Put the mixed solution into a vacuum-sealed bag and remove the air.

[0053] (2) Then the mixed solution was irradiated with an electron beam. The electron beam current intensity was set to 5 mA and the irradiation dose was 300 kGry, and the irradiated sample was obtained.

[0054] (3) The irradiated sample was washed three times with ethanol and deionized water respectively, and then placed in a vacuum drying oven and dried at 60 degrees Celsius for 12 hours to obtain the iron-based MOF electrocatalyst synthesized by electron beam irradiation.

[0055] 2. Preparation of KOH electrolyte

[0056] Dissolve 5.6 g of KOH in 50 mL of ultrapure water. After the KOH solution has completely dissolved and cooled, dilute to volume in a 100 mL volumetric flask.

[0057] 3. Preparation of Nickel Foam

[0058] A piece of nickel foam was immersed in a 1 mol / L hydrochloric acid solution and sonicated for 10 minutes. The surface was then treated with an acetone solution and sonicated for 10 minutes. Finally, it was sonicated with ethanol and deionized water for 30 minutes each.

[0059] 4. Preparation of the working electrode

[0060] Weigh 3 mg of iron-based MOF sample and disperse it in a mixed solution of 160 μL deionized water and 60 μL ethanol, then sonicate until homogeneous. Add 20 μL of Nafion and sonicate for 30 minutes. Slowly add 120 μL of the dispersion to pre-treated nickel foam using a pipette, and allow to dry in a vacuum oven for 2 hours to successfully prepare the iron-based MOF working electrode.

[0061] Example 3:

[0062] 1. Preparation of iron-based MOF electrocatalysts

[0063] (1) Prepare a mixed solution by mixing FeCl3·6H2O, isophthalic acid and N,N-dimethylformamide in a molar ratio of 1:1:280. Put the mixed solution into a vacuum-sealed bag and remove the air.

[0064] (2) Then the mixed solution was irradiated with an electron beam. The electron beam current intensity was set to 5 mA and the irradiation dose was 400 kGry, and the irradiated sample was obtained.

[0065] (3) The irradiated sample was washed three times with ethanol and deionized water respectively, and then placed in a vacuum drying oven and dried at 60 degrees Celsius for 12 hours to obtain the iron-based MOF electrocatalyst synthesized by electron beam irradiation.

[0066] 2. Preparation of KOH electrolyte

[0067] Dissolve 5.6 g of KOH in 50 mL of ultrapure water. After the KOH solution has completely dissolved and cooled, dilute to volume in a 100 mL volumetric flask.

[0068] 3. Preparation of Nickel Foam

[0069] A piece of nickel foam was immersed in a 1 mol / L hydrochloric acid solution and sonicated for 10 minutes. The surface was then treated with an acetone solution and sonicated for 10 minutes. Finally, it was sonicated with ethanol and deionized water for 30 minutes each.

[0070] 4. Preparation of the working electrode

[0071] Weigh 3 mg of iron-based MOF sample and disperse it in a mixed solution of 160 μL deionized water and 60 μL ethanol, then sonicate until homogeneous. Add 20 μL of Nafion and sonicate for 30 minutes. Slowly add 120 μL of the dispersion to pre-treated nickel foam using a pipette, and allow to dry in a vacuum oven for 2 hours to successfully prepare the iron-based MOF working electrode.

[0072] Example 4

[0073] 1. Preparation of iron-based MOF electrocatalysts

[0074] (1) Prepare a mixed solution by mixing FeSO4, terephthalic acid and N,N-dimethylformamide in a molar ratio of 1:1:250, put the mixed solution into a vacuum-sealed bag and remove the air.

[0075] (2) Then the mixed solution was irradiated with an electron beam. The electron beam current intensity was set to 7 mA and the irradiation dose was 500 kGry, and the irradiated sample was obtained.

[0076] (3) The irradiated sample was washed three times with ethanol and deionized water respectively, and then placed in a vacuum drying oven and dried at 60 degrees Celsius for 12 hours to obtain the iron-based MOF electrocatalyst synthesized by electron beam irradiation.

[0077] Example 5

[0078] 1. Preparation of iron-based MOF electrocatalysts

[0079] (1) Prepare a mixed solution by mixing Fe(NO3)2·6H2O, terephthalic acid and N,N-dimethylformamide in a molar ratio of 1:1:250. Put the mixed solution into a vacuum-sealed bag and remove the air.

[0080] (2) Then the mixed solution was irradiated with an electron beam. The electron beam current intensity was set to 10 mA and the irradiation dose was 600 kGry, and the irradiated sample was obtained.

[0081] (3) The irradiated sample was washed three times with ethanol and deionized water respectively, and then placed in a vacuum drying oven and dried at 60 degrees Celsius for 12 hours to obtain the iron-based MOF electrocatalyst synthesized by electron beam irradiation.

[0082] Comparative Example 1

[0083] RuO2 as working electrode

[0084] Comparative Example 2

[0085] 1. Synthesis of iron-based MOFs by a solvothermal method

[0086] FeCl3·6H2O, terephthalic acid, and N,N-dimethylformamide were mixed and stirred for 60 minutes in a molar ratio of 1:1:280. The mixture was then transferred to a hydrothermal reactor and reacted at 150 degrees Celsius for 15 hours.

[0087] After cooling to room temperature, the crystals are taken out, washed three times by centrifugation with ethanol and deionized water, and then dried in a vacuum drying oven at 60 degrees Celsius for 12 hours to obtain iron-based MOF crystals synthesized by solvothermal method.

[0088] 2. Preparation of KOH electrolyte

[0089] Dissolve 5.6 g of KOH in 50 mL of ultrapure water. After the KOH solution has completely dissolved and cooled, dilute to volume in a 100 mL volumetric flask.

[0090] 3. Preparation of Nickel Foam

[0091] A piece of nickel foam was immersed in a 1 mol / L hydrochloric acid solution and sonicated for 10 minutes. The surface was then treated with an acetone solution and sonicated for 10 minutes. Finally, it was sonicated with ethanol and deionized water for 30 minutes each.

[0092] 4. Preparation of the working electrode

[0093] Weigh 3 mg of iron-based MOF sample and disperse it in a mixed solution of 160 μL deionized water and 60 μL ethanol, then sonicate until homogeneous. Add 20 μL of Nafion and sonicate for 30 minutes. Slowly add 120 μL of the dispersion to pre-treated nickel foam using a pipette, and allow to dry in a vacuum oven for 2 hours to successfully prepare the iron-based MOF working electrode.

[0094] Electrocatalytic applications

[0095] 1. Activation treatment of electrocatalysts

[0096] (1) The electrochemical oxygen evolution reaction (OER) uses a three-electrode system. The working electrode is an iron-based MOFs supported on nickel foam with an area of ​​1 square centimeter. The graphite rod electrode is the counter electrode, the Hg / HgO electrode is the reference electrode, and 1 mol / L KOH is the electrolyte.

[0097] (2) Cyclic voltammetry (CV) activation: The test was performed using a CHI 660E electrochemical workstation manufactured by Shanghai Chenhua Instrument Co., Ltd. The OER test range was 1.12-1.24V (vs. RHE), the scan rate was 100 mV / s, and the cycle was 100 times until the electrode reached a stable state.

[0098] 2. Linear Scan Voltammetry (LSV) Test

[0099] The overpotential of the prepared sample was tested by linear sweep voltammetry. The potential range of the OER test was 1-1.7V (vs. RHE), and the scan rate was 5 mV / s (using automatic IR compensation with a 90% compensation level). In alkaline electrolyte, the overpotential of the electrocatalyst prepared in Example 1 was 247 mV at 20 mA / cm².

[0100] 3. Stability Test

[0101] The stability of the prepared materials was measured using a chronopotential measurement method.

[0102] Figure 1 The XRD patterns of the iron-based MOFs samples obtained in Examples 1-3 are shown. The diffraction peaks of the samples synthesized by the irradiation method are consistent with those of the samples synthesized by the solvothermal method reported in the prior art. This result indicates that iron-based MOFs were successfully synthesized by electron beam irradiation.

[0103] Figure 2 The images show the Raman spectra of the iron-based MOFs samples obtained in Examples 1-3, which further demonstrate the successful synthesis of iron-based MOFs materials. Figure 3 The iron-based MOFs prepared by irradiation in this application have a size of approximately 300 nanometers.

[0104] The OER catalytic performance of the iron-based MOF electrocatalyst of this application was measured under alkaline conditions using cyclic voltammetry, and the results are as follows: Figure 4 As shown. The iron-based MOF electrocatalyst obtained in Example 1 of this application exhibits the best OER performance, with an overpotential of only 247 mV at a current density of 20 mA / cm², significantly lower than RuO₂ (Comparative Example 1, 260 mV), iron-based MOFs synthesized by solvothermal method (Comparative Example 2, 304 mV), and the overpotentials of Examples 2 and 3 (272 mV and 281 mV, respectively), which are also significantly lower than those of iron-based MOFs synthesized by solvothermal method (Comparative Example 2, 304 mV) and most transition metal-based catalysts. At potentials of 1.5 V or higher, the current densities of Examples 1-3 of this application are all significantly higher than those of RuO₂ and iron-based MOFs synthesized by solvothermal method.

[0105] The superior OER performance of the iron-based MOF electrocatalyst in this embodiment may be due to: 1) High-energy electron beam irradiation roughens the surface, increasing the effective surface area available for contact. 2) Simultaneously, the relatively abundant positive charge and rich vacancies and defects on the sample surface optimize the adsorption of oxygen-containing intermediates, effectively promoting catalytic efficiency. 3) Because the iron-based MOF electrocatalyst sample synthesized by electron beam irradiation contains abundant polarons, the electric field generated by the polarons accelerates the adsorption of hydroxyl groups in the electrolyte by the catalyst and promotes the transformation of the metal active center to the oxygen-containing metal transition state, resulting in faster OER reaction kinetics.

[0106] The stability of the catalyst prepared in Example 1 was measured using chronopotential measurement. Figure 5 As shown, the material maintained a stable potential even after reacting for 12 hours at a current density of 20 mA / cm², indicating that the material described in this invention possesses excellent chemical stability. Abundant vacancies and defects, a relatively rough surface, and the electric field generated by polarons contribute to the excellent OER performance, rapid reaction kinetics, abundant active sites, rapid charge transfer capability, and long-term electrochemical stability of the iron-based MOF electrocatalyst in this embodiment.

[0107] The specific embodiments of this application have been described in detail above, but they are merely examples, and this application is not limited to the specific embodiments described above. For those skilled in the art, any equivalent modifications and substitutions to this application are also within the scope of this application. Therefore, all equivalent changes and modifications made without departing from the spirit and scope of this application should be covered within the scope of this application.

Claims

1. An electrocatalytic method, characterized in that, Using iron-based MOFs as electrocatalysts, wherein the electrocatalyst is an electrochemical oxygen evolution catalyst, the steps of the iron-based MOFs preparation method include: A salt containing Fe ions and an organic ligand are dissolved in a solvent to obtain a mixed solution; the Fe ions are Fe... 3+ and / or Fe 2+ The organic ligands are selected from: terephthalic acid and isophthalic acid; The air in the mixed solution is removed, and the mixed solution is irradiated with an electron beam; After irradiation, the collected solids can be used to obtain iron-based MOFs.

2. The electrocatalytic method according to claim 1, characterized in that, Salts containing Fe ions are selected from ferric ammonium sulfate, ferric nitrate, ferrous nitrate, ferric acetate, ferrous acetate, ferric oleate, ferrous oleate, ferrous lactate, ferrous lactate, ferrous succinate, ferric oxalate, ferrous oxalate, and ferric ammonium citrate.

3. The electrocatalytic method according to claim 1, characterized in that, The solvent is an aprotic polar solvent.

4. The electrocatalytic method according to claim 3, characterized in that, The solvent is selected from N,N-dimethylformamide, dimethyl sulfoxide, acetone, methyl ethyl ketone, pyridine, acetonitrile, and tetrachloromethane.

5. The method according to claim 1, characterized in that, The molar ratio of the Fe-containing salt, organic ligand, and solvent is (1-10):(1-10):(10-1000).

6. The method according to claim 5, characterized in that, The molar ratio of the Fe-containing salt, organic ligand, and solvent is (1-10):(1-10):(50-800).

7. The method according to claim 6, characterized in that, The molar ratio of the Fe-containing salt, organic ligand, and solvent is (1-10):(1-10):(100-500).

8. The method according to claim 1, characterized in that, During the electron beam irradiation process The electron beam current intensity is 0.1-50 mA; the electron beam irradiation dose is 10-5000 kGrey.

9. The method according to claim 8, characterized in that, During the electron beam irradiation process, the electron beam current intensity is 0.3-40 mA.

10. The method according to claim 9, characterized in that, During the electron beam irradiation process, the electron beam current intensity is 0.5-30 mA.

11. The method according to claim 10, characterized in that, During the electron beam irradiation process, the electron beam current intensity is 0.7-25 mA.

12. The method according to claim 11, characterized in that, During the electron beam irradiation process, the electron beam current intensity is 1-20 mA.

13. The method according to claim 12, characterized in that, During the electron beam irradiation process, the electron beam current intensity is 3-15 mA.

14. The method according to claim 13, characterized in that, During the electron beam irradiation process, the electron beam current intensity is 5-10 mA.

15. The method according to claim 8, characterized in that, During the electron beam irradiation process, the electron beam irradiation dose is 20-4000 kGrey.

16. The method according to claim 15, characterized in that, During the electron beam irradiation process, the electron beam irradiation dose is 30-3000 kGrey.

17. The method according to claim 16, characterized in that, During the electron beam irradiation process, the electron beam irradiation dose is 40-2000 kGrey.

18. The method according to claim 17, characterized in that, During the electron beam irradiation process, the electron beam irradiation dose is 50-1000 kGrey.

19. The method according to claim 18, characterized in that, During the electron beam irradiation process, the electron beam irradiation dose is 60-800 kGrey.

20. The method according to claim 19, characterized in that, During the electron beam irradiation process, the electron beam irradiation dose is 70-600 kGrey.

21. The method according to claim 20, characterized in that, During the electron beam irradiation process, the electron beam irradiation dose is 80-500 kGrey.

22. The method according to claim 21, characterized in that, During the electron beam irradiation process, the electron beam irradiation dose is 90-400 kGrey.

23. The method according to claim 22, characterized in that, During the electron beam irradiation process, the electron beam irradiation dose is 100-300 kGrey.

24. The method according to claim 23, characterized in that, During the electron beam irradiation process, the electron beam irradiation dose is selected from 120 kGy, 150 kGy, 180 kGy, 200 kGy, 230 kGy, 250 kGy, and 280 kGy.

25. The method according to claim 1, characterized in that, The collected solids are washed with a second solvent, wherein the second solvent is selected from water, alcohol, phenol, ether, aldehyde, ketone, ester, tetrahydrofuran, hydrocarbon, acetonitrile, pyridine, and carbon disulfide.

26. The method according to claim 25, characterized in that, The second solvent is selected from: water, ethanol, methanol, isopropanol, phenol, diethyl ether, petroleum ether, propylene oxide, dioxane, acetone, methyl ethyl ketone, methyl butanone, methyl isobutyl ketone, methyl acetate, ethyl acetate, propyl acetate, benzene, toluene, chlorobenzene, pentane, octane, hexane, dichloromethane, chloroform, trichloropropane, dichloroethane, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, tetrahydrofuran, pyridine, and carbon disulfide.

27. The method according to claim 25, characterized in that, The collected solids were washed with a second solvent and then dried at a temperature not exceeding 100°C.

28. The method according to claim 27, characterized in that, The drying temperature should not exceed 80℃.

29. The method according to claim 28, characterized in that, The drying temperature should not exceed 70℃.

30. The method according to claim 29, characterized in that, The drying temperature should not exceed 60℃.

Citation Information

Patent Citations

  • Application of ionization radiation source in preparation of porous crystalline material

    CN111499879A

  • Fe-doped Ni-MOF nanosheet as well as preparation method and application thereof

    CN113563596A